Fracture clinic redesign: improving standards in patient care and interprofessional education (Swiss Medical Weekly, 2012)
INTRODUCTION: Current fracture clinic models, especially with the advent of reductions in junior doctors’ hours, may limit outpatient trainee education and patient care. We have designed a new fracture clinic model, involving an initial consultant-led case review focused on patient management and trainee education. METHODS: Prospective outcomes for all new patients attending the redesigned fracture clinic over a 3-week period in 2010 (n = 240) were compared with a historical cohort from the same period in 2009 (n = 296). The primary outcome measure was the proportion of patients with direct consultant input. Secondary outcome measures included patient discharge rates, return rates, use of the nurse-led fracture clinic and the incidence of adverse event reporting. Trainees attending each clinic completed a five-point Likert questionnaire assessing the adequacy of education, support, staff morale and standards of patient care, before and after introduction of the clinic redesign. Using a separate Likert questionnaire, emergency room (ER) staff were evaluated to determine the impact of the new style clinic on their education, daily practice and interprofessional relations. Adverse events were gathered from the ‘incident record 1’ (IR1) reporting system. RESULTS: The percentage of cases given consultant input increased significantly from 33% in 2009 to 84% in 2010 (p